PENGARUH KONTROL PERILAKU DAN KEPERCAYAAN TERHADAP PRODUKTIVITAS PRODUK HOME INDUSTRI DI KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Renayani, Renayani; M., Saleh; Asrida, Asrida (Ekonomika Journal, 2023)
This research aims to analyze the influence of behavioral control and trust on the productivity of home industry products in Peusangan District, Bireuen Regency. Quantitative research and analysis using a multiple linear regression model approach. The results of this research state that behavioral control and trust partially influence the productivity of home industry products in Peusangan District. And simultaneously, behavioral control and trust influence the productivity of home industry products in Peusangan District. Where trust has a higher influence